Metaphysics of theater performance (Al-Academy, 2023)
The research explores through its three parts, to search for the unconscious and the collective unconscious in order to identify the per-formative stimuli and motives and their motivation to produce a performance that is consistent with the metaphysics of the myth or the epic and its different characters from other human characters. The paper also explores in its second section a sort of sacred performance energy. Together, along with motivating the mind and engaging the subconscious, comes a metaphysical text and with its characters and epic events.